The Influence of Your Neighbors' Religions on You, Your Attitudes and Behaviors, and Your Community. (28th January 2019) - Olson, Daniel V A
Abstract: Weber argued that the predominance of particular religious subcultures in a geographic area can influence general cultural values which, in turn, affect the values, attitudes, and secular behaviors of everyone living in an area. Not until recently have methodological advances and greater access to geographically linked data made it easier for contemporary researchers to reexamine these kinds of questions. After discussing barriers to such research, I review example studies that demonstrate that religious groups that predominate in an area can influence the behavior and attitudes of all people living in that area. Moreover, these influences act upon a broad range of attitudes (e.g., tolerance, trust), behaviors (e.g., divorce), and community-level outcomes (e.g., crime rates, infant and adult mortality rates). Sociologists of religion should expand upon this promising agenda as a way of contributing to the broader discipline of sociology and to general knowledge concerning the influences of religion upon society.